Effects of a Teaching Personal and Social Responsibility Model Intervention in Competitive Youth Sport - Carreres-Ponsoda, Federico; Escartí, Amparo; Jimenez-Olmedo, Jose Manuel; Cortell-Tormo, Juan M. (Frontiers in Psychology, 2021)
The aim of this study was to implement the teaching personal and social responsibility (TPSR) model in a competitive context analyzing the differences between the intervention and the control group on personal and social responsibility, prosocial behaviors, and self-efficacy in youth soccer players. Participants were 34 youth soccer players between the ages of 14 and 16 years old (15.18 ± 0.72) divided into two different soccer teams of 17 members, corresponding to the control and intervention groups. The implementation of the TPSR model took place during 9 months, including initial and ongoing coach training (3 months), program implementation (three sessions per week lasting 90 min during 6 months), and a series of expert-led seminars for athletes (one session per week lasting 90 min during 4 months). The questionnaires used to collect data were the Personal and Social Responsibility Questionnaire, Prosocial Behavior Scale, and two Children’s Self-efficacy Scales. Results indicated that the TPSR intervention group obtained an increase in post-test levels of personal and social responsibility, prosocial behavior, and self-efficacy due to the application of the TPSR model compared with control group that used a conventional sport teaching methodology. The conclusion is that the TPSR model has the potential to be adapted and implemented with flexibility in youth sport competition contexts in order to improve personal and social responsibility, prosocial behavior, and self-efficacy.